Internship report on Blueclinical phase I unit - Moreira, Paula Cristina Leão (2018)
Bioavailability/Bioequivalence clinical trials are a promising area in Pharmaceutical R&D and it is very interesting being involved in this field. During the internship, I practiced assistance activities to Bioavailability/Bioequivalence clinical trials and this was my target for intervention within Blueclinical during ten months. During this time I also had opportunity to exercise nursing research activities due to my previous training in the area. This report aims to describe the activities in which I was involved, the learning points and the experience achieved about the conduction of Bioavailability/Bioequivalence clinical trials. During the internship I have developed clinical trial assistance activities and I learned a lot about the process of trial conduction, from the submission to the authorities to get their approvals until the process of reporting the results This job was a challenge and a continuous learning process. At the end of this period, I feel it was a rewarded effort and I would like to keep developing my skills in this area.